2018
DOI: 10.1016/j.esxm.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Scandinavian Prostate Cancer Patients’ Sexual Problems and Satisfaction With Their Sex Life Following Anti-Cancer Treatment

Abstract: IntroductionActive prostate cancer treatment is often associated with significant adverse physiological and psychological effects including significant sexual problems. Most studied among these sexual problems is erectile dysfunction while related sexual bothers such as overall sexual function and satisfaction with one’s sex life are much less studied.AimTo investigate problems related to erectile functioning, orgasmic ability, sexual function, and satisfaction with one’s sex life among a cohort of Scandinavia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Although patients who reach their baseline erectile function will not necessarily need to manage sexual satisfaction, 10,80 the erectile function score is not correlated with overall satisfaction. In the literature, several factors in addition to erectile function were found to be associated with sexual satisfaction: sexual desire, intensity of orgasm, sexual self‐esteem, age, time since diagnosis, relationship variables, and psychological variables such as depression and anxiety 80–84 . There is a significant association between depressive symptoms and erectile dysfunction, and depressive symptoms may contribute to a delay in the improvement of sexual satisfaction in patients with ED due to RARP 83,85 .…”
Section: Psychological Concernsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although patients who reach their baseline erectile function will not necessarily need to manage sexual satisfaction, 10,80 the erectile function score is not correlated with overall satisfaction. In the literature, several factors in addition to erectile function were found to be associated with sexual satisfaction: sexual desire, intensity of orgasm, sexual self‐esteem, age, time since diagnosis, relationship variables, and psychological variables such as depression and anxiety 80–84 . There is a significant association between depressive symptoms and erectile dysfunction, and depressive symptoms may contribute to a delay in the improvement of sexual satisfaction in patients with ED due to RARP 83,85 .…”
Section: Psychological Concernsmentioning
confidence: 99%
“…In the literature, several factors in addition to erectile function were found to be associated with sexual satisfaction: sexual desire, intensity of orgasm, sexual self-esteem, age, time since diagnosis, relationship variables, and psychological variables such as depression and anxiety. [80][81][82][83][84] There is a significant association between depressive symptoms and erectile dysfunction, and depressive symptoms may contribute to a delay in the improvement of sexual satisfaction in patients with ED due to RARP. 83,85 We must clarify whether this depressive condition may be caused by ED per se or the combination of the other sexual dysfunction symptoms.…”
Section: Psychological Concernsmentioning
confidence: 99%
“…Of men undergoing PC therapy, 72% to 92% experience diminished sexual health that is likely to persist after successful completion of treatment 59 . Following definitive therapy, patients may experience erectile dysfunction, climacturia, penile shortening, altered orgasms and loss of libido, which can significantly impact their intimate relationships 60 .…”
Section: Role Of the Nurse Specialist In Managing Adverse Drug Eventsmentioning
confidence: 99%
“…2,3 Sexual dysfunction, the inability to achieve or maintain sexual activity due to less sexual desire or erectile dysfunction (ED), is one of the concerning adverse effects of radical therapies for prostate cancer. [4][5][6] Studies have shown that men on AS have lower risk of sexual dysfunction (and are more often sexually active) than men who undergo surgery/local therapy. [5][6][7][8] Preserving sexual function is one of the major reasons that patients delay treatment.…”
Section: Introductionmentioning
confidence: 99%